Is advertising under-resourced in a growth market? Intangible endogeneity and informed trading issues - Hodgson, Allan; Lhaopadchan, Suntharee; Ratiu, Raluca Valeria (Wiley, 2017)
We examine advertising value relevance when advertising competes against other intangibles for scarce funding in a growth market. Manufacturing firms that strategically increase advertising are rewarded—they provide a direct and indirect Granger lead to stock prices above sales and income. In service firms, stock prices and intangible budgets are independently determined—with increased expenditures beyond established (optimal) levels penalised. Insider trading, conditioned on advertising, extracts 60-day arbitrage returns of 22.5 percent, consistent with VECM signals. Highlighted is the importance of maintaining optimum intangible budgets, observing cues from informed traders and in identifying analyst following that constrains insider rent extraction.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura